Drivers of Spatial Variation in the Role of Ants as Secondary Seed Dispersers - Bottcher, C.; Peixoto, P. E. C.; Silva, W. R.; Pizo, M. A. [UNESP] (Oxford Univ Press Inc, 2016)
The spatial variation in the outcome of the interaction between secondary dispersers and seeds is superimposed upon the variation produced by primary dispersers. Investigating the factors that drive the outcome of the interactions with secondary seed dispersers thus represents an essential refinement to our understanding of the complete seed dispersal process. We studied the interactions between two ponerine ants (Pachycondyla striata Smith, 1858 and Odontomachus chelifer (Latreille, 1802)) with fruits experimentally set on the ground, and estimated the effects of ants on seedling establishment in three areas distributed along a 2-km stretch of a Brazilian Atlantic rainforest that differ in soil properties and vegetation physiognomies. We tested the hypothesis that interactions are more frequent, resulting in greater seedling establishment at the site with harsher abiotic and biotic conditions. Both ant species removed fruits frequently and have a positive effect on seedling establishment in all study areas, but fruit removal did not differ among areas, while seedling establishment was more pronounced at the site with stressful abiotic conditions. The two ant species differed in important aspects of their seed dispersal services, including the propensity to interact with seeds. As a result, both the species of ant and abiotic conditions interact at the scale of 2km to determine the fate of seeds interacting with ants, thus creating a mosaic of outcomes with variable benefits to plants.
Keywords: Atlantic Forest; Brazil; fruit removal; mutualism; plant-animal interaction